Skins, envelopes, and enclosures concepts for designing building exteriors - Yu, Mayine (Routledge, 2014)
"As an architect, you want to integrate the best building envelope construction methods, materials science, and structural principles in your work, but you need a resource to help you. With more than seventy significant case studies located in North America, South America, Europe, and Asia from prehistory to the present, this book illuminates the theory and techniques of assembling exteriors. Six chapters organized by wall types, from hand-set monolithic walls to digitally fabricated curtain walls, each have a material focus section to help you understand their intrinsic properties so that you can decide which will best keep the weather out of your building. Case studies include: Great Wall, China Israeli Supreme Court Building, Jerusalem, Ram Karmi and Ada Karmi-Melamed Fďřation Nationale du Bt́iments, Paris, Jean Prouv̌ Institut du Monde Arabe, Paris, Jean Nouvel Morgan Library, New York City, Renzo Piano Katsura Imperial Villa, Kyoto Sainsbury Center for Visual Arts, Norwich, UK, Sir Norman Foster"